Towards Electoral Justice: Redesigning an Ideal System for Enforcing Electoral Administrative Law in Indonesia? - Bagja, Rahmat; Isra, Saldi; Palguna, I Dewa Gede; Fahmi, Khairul; Ezzerouali, Souad Ahmed (Jambe Law Journal, 2025)
This article examines Indonesia’s legal framework for protecting the right to be elected, with a focus on electoral administrative law enforcement across Bawaslu, the Administrative Court (PTUN), and the Constitutional Court (MK). Building on Marc Galanter’s “justice in many rooms,” the study introduces the concept of “electoral justice in many connected rooms” to assess the coherence and effectiveness of legal remedies. Using normative, comparative, and case-based approaches, it analyzes disputes involving party officials, former convicts, and gender quota candidates. Findings reveal that institutional fragmentation and normative inconsistencies often hinder the full restoration of candidacy rights, with the General Election Commission (KPU) frequently disregarding binding decisions due to legal ambiguity or inter-agency conflict. The study identifies two key challenges; vague or retroactively applied legal norms and procedural coordination among enforcement bodies. It argues that changes to candidacy regulations must apply prospectively and that enforcement must distinguish between active and passive suffrage. The article proposes a coordinated model of electoral administrative enforcement that combines preventive and repressive measures, institutional alignment, and judicial restraint in line with the Purcell Principle. It concludes by calling for legislative reform to ensure legal certainty, institutional synergy, and meaningful protection of electoral rights